Manajemen Ketahanan Pangan pada Masyarakat Adat Citorek, Lebak, Banten - Cinta Rahmi; Haria Saputri; Moh. Tahang; Ujang Kusnaedi; Surtariyono Sutariyono; Tetty Nur Intan Rifia; I Dewa Ketut Suharjana; Halim Tjiwidjaja; Deden Mauli Darajat (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Citorek Village is a village that has abundant natural resources that can be developed, the natural resources owned by Citorek Village include abundant rice fields where almost every corner of the road is surrounded by beautiful rice fields because many Citorek villagers grow crops from rice, corn, chilies, and other plantation products. This research aims to find out how environmental management is carried out by the Citorek indigenous people in farming with the land cultivation rotation method. The research method used is a phenomenology-based qualitative method, which is a research method applied in various social sciences, including communication and management. The results showed that the Citorek indigenous community, Lebak, Banten, managed to carry out environmental management very well. The Citorek Customary Chief or Jaro is the driving force in determining the time and method of land cultivation rotation. Jaro Adat leads the five village heads in the Citorek area in all processes of community life. In this context, the Citorek indigenous people carry out a rotation culture by planting rice for six months and developing carp for the next six months, the schedule of which is adjusted according to the direction of Jaro Adat. In addition to the economic value obtained by the Citorek indigenous community, this rotation of land cultivation also maintains sustainable natural preservation that is so fertile in the region.